Coprinellus sect. Disseminati: Source of Gastropod Mycophagy in Bogor-Indonesia - Ivan Permana Putra; Juan Alvares Dagtonan Thamrin (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2021)
Mycophagy is the process of the organism consuming fungi. Fungal  tissue considered  as  valuable  resource  with  high  nutritional content for organisms which have the metabolic abilities to digest it. To date, there is no previously published record of animal mycophagy in Indonesia. Field observations in IPB University Campus Forest has been done to monitor mycophagy activity by any animals in sampling site. Only 1 of the 4 observasion period showed the evidence of animal mycophagy in sampling site. Mycophagous gastropod found to consume Coprinellus disseminatus fruit body as diet source. Macrofungi fruit body was eaten within two to three minutes. The snail only consume the pileus part of fruit body of Coprinellus disseminatus. It showed to use it’s anterior tentacles to pick the stages of fruit body. The gastropod tend to prefer mature fruitbody, yet the the reasons are still not clear. This is the first report of animal mycophagy evidence in Indonesia.